看護の現場からのメッセージ：安全な与薬のために薬理学教育に何を求めるか - 小見山, 智恵子 (日本薬理学会年会要旨集, 2020)
Most patients admitted to the hospital receive some form of medication. The nurse prepares the medicine, and checks as the final performer of pharmacotherapy, the "right patient" "right drug" "right purpose" "right dose" " right route" and the "right time", and give the patient medication. Furthermore, it confirms that the medicine is surely carried into the patient's body, observes the patient's reaction, and plays a role in quickly responding to any abnormalities. The medication by nurses is an extremely important and responsible task.Will new nurses just graduate start working in hospital with the knowledge, skills, and judgment necessary to safely perform this important task? Their knowledge about drugs is fragmented, they do not integrate knowledge about diseases and conditions, drug actions and mechanisms, treatment guidelines and protocols. And they have not been acquired techniques of the medication intravenous injections, gastric catheter injection etc. They need to learn a lot after graduating from nurse school.In the current acute ward, patients with different clinical conditions and treatment methods are admitted to the hospital, and the patient condition and drugs involved by nurses are diversified. It has become a difficult environment for nurses to safely carry out medication operations. Incidents related to nurse medications have not diminished, and nurses are concerned that they may become parties to the incident.In hospital, we are exploring how to build work environments and educational systems for safety medication. In order for nurses to administer medicines that are safe for both patients and themselves, they must understand the dangerous environment around them and the knowledge and skills that are lacking in themselves. It is important that they can properly seek assistance from the surrounding staff.In this symposium, I would like to think about what can be strengthened by basic education at school and what should be strengthened by on-the job education in order for nurses to administer medication safely.